The effect of retail mix on passengers’ motivation to shop at airport terminal outlets / Siti Zaleha Sahak … [et al.] - Sahak, Siti Zaleha; Mohd Yusof, Abdul Wahab; Mudri, Erni Yusliza; Saidin, Sadinar (Universiti Teknologi MARA, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2018)
Retailing represents one of the commercial activities contributing to the non-aeronautical source of revenue to most airport operators. In this research, Kuala Lumpur International Airport 2 or better known as KLIA2 represents the focus of the study. KLIA2 is built to cater to low-cost carriers and the airport is built on the concept of ‘a mall in the airport'. There are two commercial areas designated for passengers to shop: gateway@KLIA2 and terminal outlets. These create more choices for passengers to shop and at the same time increase competition among the retailers. Focusing on the terminal outlets, this study aims to examine the influence of airport retail mix elements on passengers’ motivation to shop. The factors examined were the location of the outlets, promotion, personnel, atmosphere of the outlets, product mix and price. The study utilized survey method and questionnaire was designed to gather data from departing passengers for both domestic and international sectors. The self-administered questionnaires generated a total of 307 usable responses. Data were analyzed using SPSS. The result of multiple regression analysis showed that the key airport retail mix element which motivates passengers to shop is the location of the outlet, followed by promotion and product mix. Recommended strategies for airport retailing were highlighted.